Upaya Guru PAI dalam Meningkatkan Literasi Al Qur’an Peserta Didik di SMKN 6 Surakarta - Marliana, Hanifah; Inayati, Nurul Latifatul (Lembaga Penelitian dan Pengabdian kepada Masyarakat (Center for Research and Community Services), Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2024)
This study used qualitative research. The study focused on the lack of attention to the recitation of the Qur'an in public schools which resulted in many students facing difficulties when reading the Qur'an. Therefore, Islamic Religious Education (PAI) teachers at SMK Negeri 6 Surakarta actively make various efforts to improve Qur'an literacy in the school environment. The purpose of this study was to identify the efforts made by PAI teachers in the school. The research was conducted for one month at SMK Negeri 6 Surakarta. The efforts made include familiarizing students with reading the Qur'an before starting learning activities, doing tadabbur al Qur'an, and providing motivation to students.